The modern view of macroeconomics : some critical reflections - Palacio Vera, Alfonso (Documento de trabajo ;, 2002)
Romer has proposed an alternative macroeconomic framework, i.e., the IS-MP-IA model. Its proponents claim that it constitutes a "modern" view of macroeconomics. We show that the new framework is closely attached to the neoclassical synthesis and, in addition, fails to take account of: (i) the recent empirical evidence on the short-run output-inflation trade-off, (ii) the recent work and evidence on the interdependence of aggregate demand and supply, (iii) the lirnits of monetary policy and (iv) the consequences for demand-management policy of (i), (ii) and (iii). Once all these aspects are incorporated, we have that short-run stabilization policy is non-neutral in the long run, loanable funds theory becomes irrelevant and aggregate demand becomes the crucial exogenous variable in the short run and, perhaps, also in the long run.